BALANCE OF POWER AFTER UKRAINE WAR - TRANSATLANTIC FUTURES: NATO 2030 (Security Dialogues, 2024)
The outcome of the conflict in Ukraine will bring fundamental political, military, economic, security and social consequences on global scale, comparable with previous historical events of Westphalian Peace, The Concert of Great Powers, Versailles system, YaltaPotsdam system and the end of the Cold War. The aim of this paper is to analyze possible scenarios of Ukraine war and possible global strategic consequences of this conflict, including development of transatlantic link of Europeansecurity and development of NATO Alliance until 2030. The outcome of the Ukrainian conflict will clearly determine future of political and institutional capability of the West, including NATO and European Union. The same issue will apply for Russian Federation and future of non-West integration platforms, including BRICS, SCO and CSTO. Perspective of multi-polar global and regional security order over unipolar – the United States led global security order.Therefore, possibility of decreasing political, military, institutional and economic power of the United States, NATO and EU and possibility of further integration and development of BRICS, SCO, and CSTO is plausible. However, NATO Alliance has developed necessary strategies and taken necessary decisions in order to counter security challenges and threats stemming from China, Russian Federation and other global and regional actors. Madrid NATO Summit in June of 2022 has approvednew NATO Strategic Concept (NSC) which will remain relevant until 2030. NSC outlines necessary decisions, capabilities and actions in order to safeguard territory of the Alliance via strengthening the Eastern flank of the Alliance, substantially increase number of NATO High Readiness Forces and organize other activities in order to facilitate political and military development of NATO. Agenda NATO 2030 is ambitious agenda which will also determine future of trans-Atlantic link and future of the Alliance. The Agenda set out for necessary steps and actions to ensure that NATO remains ready, strong and united for a new era of increased political, military and economic competition with China and Russian Federation, and other emerging regional powers. The Agenda 2030 reveals strategic proposals for NATO development- deeper political and military consultations among the NATO Allies, strengthened deterrence and defense, improved resilience, preservation of technological edge of NATO Alliance, uphold the Rules- based international order, maintenance of NATO Open Door Policy, boost training and capacity building, combat and adapt to climate change, investing in NATO financial capability and allocation of recourses for the defense budgets of member states of the Alliance.